The Merdeka Belajar Kampus Merdeka Program: An Analysis of the Success Factors - Defrizal Defrizal; Appin Purisky Redaputri; Vonny Tiara Narundana; Nurdiawansyah Nurdiawansyah; Yanuarius Yanu Dharmawan (Lembaga Sosial Rumah Indonesia, 2022)
The background of this research is that the implementation of the MBKM policy has not been fully implemented, obstacles such as human resources and supporting facilities are not yet ready. So, it is necessary to know what are the factors that influence the successful implementation of Merdeka Belajar Kampus Merdeka Program, especially at the Universitas Bandar Lampung. This study uses a qualitative approach with data collection methods using In-Depth Interviews. The results obtained are the factors that influence the success of the implementation of the Merdeka Belajar Kampus Merdeka Program, namely the commitment and vision of the university leadership towards the implementation of the Merdeka Belajar Kampus Merdeka Program, the existence of a special unit that is responsible for the implementation of the Merdeka Belajar Kampus Merdeka Program, the support and commitment of partners, the same positive mindset from the entire academic community regarding the Merdeka Belajar Kampus Merdeka, the role of active and optimal supervisors, the role of active, initiative and creative students, the role of other academics regarding the administration of activities, the existence of standard operating procedures references, curriculum conformity planning, ect.